Analisis Self Management dan Pengontrolan Tekanan Darah pada Pasien Hipertensi di Puskesmas Lima Puluh Kota Pekanbaru - Desti Puswati; Novi Yanti; Dekriani Yusela (HEALTH CARE : JURNAL KESEHATAN, 2021)
Due to the Covid-19 pandemic, blood pressure management control which is usually carried out at the Puskesmas is recommended to be measured or home monitored to prevent the transmission of Covid- 19. The third highest case which happened in Puskesmas Lima Puluh Kota is hypertension. The purpose of this study was to analyze hypertensive patient on Self Management and blood pressure monitoring at Puskesmas Lima Puluh Kota in Pekanbaru city. The descriptive desained study patient with hypertention involves 66respondent with probability sampling technique.The measuring instrument used was the Hypertension Self-Management Behavior Quetionnaire (HSMBQ, while the instrument for controlling blood pressure uses the measurement of the respondent's blood pressure in the last month. The statistical test used in this study is the frequency distribution. The resultsshowed that self management was moderate category 66.7% and blood pressurecontrol was in the majority of patients hypertension patients is not controlled, namely 68.2%. Suggestions for health services to provide health education to patient with hypertension about self-management so that patients do not have a relapse who are at risk of being easily infected with covid 19